Neurolymphomatosis of T‐Cell Origin in a Dog - Marie‐Kerstin Müller; Michaela Irmscher; Nadja Goldbach; Alexander F. H. Haake; Olivia Kershaw; Penelope A. Baloi (Journal of Veterinary Internal Medicine)
ABSTRACT A 10‐year‐old mixed‐breed dog was presented with progressive neurological deficits suggestive of polyneuropathy. CT and MRI revealed no relevant abnormalities, whereas the CSF analysis showed a marked lymphocytic pleocytosis, immunocytochemically classified as T‐cell lymphoma. Chemotherapy ensued with no improvement of clinical signs. Cerebrospinal fluid reanalysis still revealed a mild lymphocytic pleocytosis. MRI of the brain and spinal cord solely showed a reduced ventral subarachnoid and epidural space (Th11‐L2) and mild enlargement of the central canal in this area. Postmortem examination revealed thickening of the spinal nerve roots and ganglia. Histologically, a marked intraspinal‐subdural and intraneural, as well as intra‐ganglionic, infiltration by large lymphocytes in the peripheral nervous system was visible. Immunohistochemically, the infiltrating lymphoblasts were CD3 positive, confirming T‐cell origin. Neurolymphomatosis is a rarely described neoplastic disease in dogs. The present case highlights the importance of analysis of CSF in neurologically abnormal dogs.